Pengaruh Fee Audit, Komite Audit, dan Ukuran Perusahaan Terhadap Kualitas Audit - Sukadi, Sukadi; Defel Septian; Khairunnisa, Khairunnisa (Jurnal Riset Manajemen dan Akuntansi, 2026)
Audits aim to provide assurance on the fairness of the presentation of financial information, making audit quality a crucial factor in maintaining stakeholder trust. The importance of audit quality is reflected in the case of PT Express Transindo Utama Tbk (PT TAXI), which demonstrated audit quality issues and led to a decline in public trust in companies and Public Accounting Firms (KAP), particularly regarding the differences in audit quality between Big Four and Non-Big Four KAPs. This study aims to analyze the influence of audit fees, audit committees, and company size on audit quality in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period. The study employed a quantitative method with purposive sampling, resulting in 13 companies with a total of 52 observational data. Audit quality was measured using a dummy variable, with companies audited by Big Four KAPs assigned a value of 1 and Non-Big Four KAPs assigned a value of 0. Data were obtained from the company’s financial statements and annual reports and analyzed using logistic regression with SPSS version 26. The results showed that audit fees, audit committees, and company size had a significant positive effect on audit quality. These findings support agency theory and demonstrate the importance of auditor quality, audit committee effectiveness, and company size in improving audit quality. The policy implications of this research are for the Financial Services Authority (OJK) and the Indonesian Stock Exchange (IDX) to strengthen oversight and regulation to improve audit quality in public companies.